Audience segmentation to improve targeting of conservation interventions for hunters. Issue 4 (9th January 2019) - Jones, Sorrel; Keane, Aidan; St John, Freya; Vickery, Juliet; Papworth, Sarah
Abstract: Audience segmentation could help improve the effectiveness of conservation interventions. Marketers use audience segmentation to define the target audience of a campaign. The technique involves subdividing a general population into groups that share similar profiles, such as sociodemographic or behavioral characteristics. Interventions are then designed to target the group or groups of interest. We explored the potential of audience segmentation for use in defining conservation target groups with a case study of hunters in Liberia. Using 2 data sets describing households ( n = 476) and hunters ( n = 205), we applied a clustering method in which infinite binomial mixture models group hunters and households according to livelihood and behavior variables and a simple method to define target groups based on hunting impact (hunting households and high‐impact hunters). Clusters of hunters and households differed in their experiences with confiscation of catch at roadblocks and participation in livelihood‐support programs, indicating that these interventions operate unevenly across subsets of the population. By contrast, the simple method masked these insights because profiles of hunting households and high‐impact hunters were similar to those of the general population. Clustering results could be used to guide the development of livelihood and regulatory interventions. For example, a commonly promoted agricultural activity, cocoa farming, was practiced by only 2% (out of 87) of the largest hunter cluster of nonlocal gun hunters but was prevalent among local trappers, suggesting that assistance aimed at cocoa farmers is less appropriate for the former group. Our results support the use of audience segmentation across multiple variables to improve targeted intervention designs in conservation. Abstract : Article impact statement : Audience segmentation defines hunter groups for conservation intervention. Abstract : Segmentación del Público para Mejorar la Focalización de las Intervenciones de Conservación para los Cazadores Resumen: La segmentación del público podría ayudar a mejorar la efectividad de las intervenciones de conservación. Los publicistas utilizan la segmentación del público para definir al público focal de una campaña. La técnica incluye la subdivisión de una población general en grupos que comparten perfiles similares, como las características socio‐demográficas o de comportamiento. Después se diseñan las intervenciones para enfocarse en el grupo o los grupos de interés. Exploramos el potencial de la segmentación del público en el uso de la definición de grupos con objetivos de conservación usando el estudio de caso de los cazadores en Liberia. Con dos conjuntos de datos de descripciones de los hogares ( n = 476) y de los cazadores ( n = 205) aplicamos un método de agrupación en el cual los modelos de mezcla binomial infinita agruparon a los cazadores y a los hogares de acuerdo a las variables de sustento y de comportamiento. También aplicamos un método simple para definir los grupos focales con base en el impacto de la caza (hogares de cazadores y cazadores de alto impacto). Los grupos de cazadores y de hogares difirieron en experiencias con la confiscación de la caza en retenes y en participación dentro de programas de apoyo al sustento, lo que indica que estas intervenciones operan disparejamente en los subconjuntos de la población. En contraste, el método simple enmascaró estas percepciones ya que los perfiles de los hogares de cazadores y de los cazadores de alto impacto fueron similares a los de la población general. La agrupación de los resultados podría usarse para guiar el desarrollo del sustento y de las intervenciones regulatorias. Por ejemplo, el cultivo de cacao, una actividad agrícola que se promueve frecuentemente, sólo lo practicaba el 2% (de 87) del mayor grupo de cazadores de los cazadores armados no locales, pero fue prevaleciente entre los trampeadores locales, lo que sugiere que la asistencia enfocada hacia los cultivadores de cacao es menos apropiada para el primer grupo. Nuestros resultados respaldan el uso de la segmentación del público en múltiples variables para mejorar los diseños de intervenciones focalizadas en la conservación. 摘要: 受众细分有助于提高保护干预措施的有效性。市场营销者用受众细分来确定活动的目标受众, 这项方法涉及将一般人群划分为具有相似特征 (如社会人口统计学或行为特征) 的多个亚群, 然后针对一个或多个亚群来设计干预措施。我们以利比亚的狩猎者为例, 探讨了受众细分在确定保护的目标群体方面的应用潜力。我们利用描述家庭 ( n = 476) 和狩猎者 ( n = 205) 的两个数据集, 采取聚类方法根据生计和行为变量用无限二项混合模型对狩猎者和家庭进行分类, 同时用一个简单方法根据狩猎影响确定了目标群体 (狩猎家庭和高影响狩猎者) 。狩猎者和家庭聚类群集间的差别在于在路障检查中被没收猎获物的经历和生计支持项目的参与情况, 表明干预措施不能均衡地作用于人群的不同亚群。相比之下, 用简单方法不能得到这些发现, 因为狩猎家庭和高影响猎人与普通人群的特征相似。聚类结果还可用于指导生计发展和监管干预。举例来说, 对于当地大力推广的可可种植这项农业活动, 外来用枪狩猎者的最大聚类群集中只有 2% 的人 (共 87 人) 参与, 但在本地设陷阱的人中参与度却很高, 这表明针对可可种植者的援助并不适用于前者。我们的结果支持了利用考虑多个变量的受众细分来提高保护中的针对性干预措施的设计。[翻译: 胡怡思; 审校: 聂永刚]